Paciente de sexo masculino de 50 años de edad con diagnóstico de fibrosis pulmonar. - Quinto Haro, Génesis Shandell (2022)
Pulmonary fibrosis is a disease that affects the lower respiratory tract and is characterized by abnormal scarring of the lung tissues, thus considerably reducing the passage of air into the blood. The main symptoms that characterize this pathology are: progressive dyspnea, persistent dry cough, precordial pain, chronic respiratory failure and hypoxemia-hypercapnia. For the diagnosis of this pathology, the patient's clinical history and complementary tests are analyzed, imaging studies such as chest X-ray and computerized axial tomography are performed. The present study is a clinical case of a 50-year-old male patient who goes to the emergency area due to signs and symptoms such as dry cough, muscle pain, mid-exertion dyspnea, fever. The realization of this clinical case has as its main objective to establish a correct treatment in the patient in order to improve their lifestyle.